2004
DOI: 10.1902/jop.2004.75.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Implant Therapy Following Liver Transplantation: Clinical and Microbiological Results After 10 Years

Abstract: This case report suggests that immunocompromised patients can be successfully rehabilitated with dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Although some animal studies have shown that cyclosporine causes impairment in bone quality and bone healing around implants and in their mechanical retention, 125-128 case series and case reports have documented successful implant rehabilitations in patients that underwent organ transplantation. [129][130][131] In conclusion, no evidence exists that immunodeficiency is a contraindication for dental implants, however the medical condition should be investigated and the clinician should consider antibiotic prophylaxis and topic antiseptics (chlorexidine) to reduce the risk of infections, following communication with the relevant physician.…”
Section: Aids and Immunocompromised Patientsmentioning
confidence: 99%
“…Although some animal studies have shown that cyclosporine causes impairment in bone quality and bone healing around implants and in their mechanical retention, 125-128 case series and case reports have documented successful implant rehabilitations in patients that underwent organ transplantation. [129][130][131] In conclusion, no evidence exists that immunodeficiency is a contraindication for dental implants, however the medical condition should be investigated and the clinician should consider antibiotic prophylaxis and topic antiseptics (chlorexidine) to reduce the risk of infections, following communication with the relevant physician.…”
Section: Aids and Immunocompromised Patientsmentioning
confidence: 99%
“…Recently, a titanium alloy with 6 wt% aluminum and 7 wt% niobium (Ti-6Al-7Nb) has been developed that offers biocompatibility 10) and sufficient corrosion resistance 11) as well as superior wear resistance 12) , strength 12,13) , ductility 13) and machinability 14) compared to CP Ti. The cone crown telescopic system is also used for attachments for implant supported prostheses [15][16][17][18][19][20][21] and this application was reported to be a viable treatment option 16) . Recently, a prefabricated cone crown telescopic system using a titanium alloy with 6 wt% aluminum and 4 wt% vanadium (Ti-6Al-4V) and gold alloy for implant superstructures has come on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Althoug all of that, publications describing cases of therapies which used implants among organ transplant recipients appeared, and the follow up of the dental implants in transplant patients showed an acceptable results near to those in healthy persons, and showed that it is possible to place dental implants in patients in the course of their long-term immunosuppressive therapy following organ transplants (17,18,19,20). so the result appeared in this case report agree with results of previous publicatios.…”
Section: Discussionmentioning
confidence: 99%